Earthworms Building Up Soil Microbiota, a Review - Medina-Sauza, Regina M.; Álvarez-Jiménez, Marycruz; Delhal, Alix; Reverchon, Frédérique; Blouin, Manuel; Guerrero-Analco, José A.; Cerdán, Carlos R.; Guevara, Roger; Villain, Luc; Barois, Isabelle (Frontiers in Environmental Science, 2019)
The positive effect of earthworms on soil processes and plant growth has been extensively documented. They enrich the soil in nutrients through their casts and improve soil structure and aeration by the burrows and galleries they form, thereby creating the functional domain called drilosphere that make them biochemical and physical ecosystem engineers. The capacity of earthworms to decompose organic matter has been attributed to the microbial communities that inhabit their digestive track or the structures they build. However, the nature and mechanisms of soil microbial community modifications and how these changes impacts soil microbial processes are still unclear. Do earthworms reduce microbial abundance and activity because they feed on microorganisms or do they select and stimulate specific microbial groups? It has been shown that the production of mucus during gut transit is responsible for a priming effect, referred to as the “Sleeping Beauty Paradox”, that enhances microbial activity, which in turn promotes the digestion of recalcitrant organic matter. Recent reports showed that specific bacterial groups increased in soils where earthworms are present. In addition, the earthworm digestive track, casts and biopores are considered hotspots for nutrient turnover with enhanced bacterial growth and potentially specific bacterial communities, that mineralize nitrogen and phosphorus or produce metabolites known for their plant growth promoting effects. The objective of this review is to synthesize the existing literature concerning the influence of earthworms on the structure and function of soil bacterial communities, as well as to understand how earthworm-induced changes in the soil microbiota would in turn impact soil processes, particularly those in the rhizosphere that are involved in plant growth and health. We propose a framework for earthworms – microbiota interactions and recommend further research to be dedicated at deciphering microbial processes occurring in the drilosphere, a hotspot where bacterial richness and diversity are enhanced and which is critical for plant-soil interactions.